Ekstraksi silika yang terkandung dalam limbah abu terbang batu bara - Joice Dorsila Susana Caroles (Jurnal Kimia Fullerene, 2019)
Coal fly ash waste contains metal oxides, one of which is silica. The presence of silica in coal fly ash allows the waste to be used directly as an adsorbent. The use of silica contained in coal fly ash can be carried out maximally by silica purification. Silica purification by extracting silica from coal fly ash aims to minimize unnecessary metal oxide levels (impurities). Analysis of silica content carried out before and after the extraction process aims to determine the levels of silica compared to other metal oxides. The procedure is done, namely sieving to separate samples from impurity material, then analyzing using SEM-EDS instruments, and then proceed with the silica extraction process. The results of the analysis showed a greater percentage of silica (SiO2) content of 67.68% compared to Al2O3 of 16.80%; while the extracted silica content was 80.42%.